Hubs of Empire : The Southeastern Lowcountry and British Caribbean - Mulcahy, Matthew, 1968- (Book collections on Project MUSE., 2014)
"The colonial Low Country (the Carolinas, Georgia) and British Caribbean made up an integrated region quite distinct from the Chesapeake, Mid-Atlantic, or New England. Like Maryland and Virginia, the greater Southeast--which formed, as Mulcahy argues, a dynamic center of the British imperial scheme in the New World--relied on staple crops and slave labor. Yet the economic and social ties that bound the Carolinas and the West Indies created quite distinct cultures, black and white alike, giving planters, e.g., a sense of taste and behavior far more tropical and Continental than the ideals that influenced tobacco planters in the Chesapeake. The location and trade patterns of the Carolinas and West Indies encouraged the purchase of slaves from sources and in numbers that ensured far greater persistence of African traditions (and threats of violence) than elsewhere. Mulcahy offers us a short book that explores this early-American/Caribbean region in the manner of our other series titles--explaining the integrity if not unity of the region and what made it so and also comparing it to other economic/cultural regions in the colonial period"--